1993
DOI: 10.1073/pnas.90.10.4480
|View full text |Cite
|
Sign up to set email alerts
|

Identification of human endogenous retroviruses with complex mRNA expression and particle formation.

Abstract: Retroviruses comprise strains with considerable disease potential in animals and humans. In addition to exogenous strains transmitted horizontally, endogenous proviruses are transmitted through the germ line. Some of these endogenous retroviruses can be pathogenic in mice and possibly in other animal species. They may also be considered as mobile genetic elements with the potential to produce mutations. In humans, genomic DNA contains numerous endogenous retroviral sequences detected by their partial relatedne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
237
0
2

Year Published

1996
1996
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(244 citation statements)
references
References 43 publications
5
237
0
2
Order By: Relevance
“…The vast majority of HERV sequences are dysfunctional due to the accumulation of multiple nonsense mutations. However, proviral loci of the HERV-K (HML-2) family of retroviral elements, of which 30 to 50 copies are estimated to reside in the haploid human genome, often contain intact open reading frames for the viral proteins Gag, Prt, Pol and Env (Lower et al, 1993;Mayer et al, 1997a,b). We have recently identi®ed an almost intact HERV-K provirus on human chromosome 7 (Mayer et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The vast majority of HERV sequences are dysfunctional due to the accumulation of multiple nonsense mutations. However, proviral loci of the HERV-K (HML-2) family of retroviral elements, of which 30 to 50 copies are estimated to reside in the haploid human genome, often contain intact open reading frames for the viral proteins Gag, Prt, Pol and Env (Lower et al, 1993;Mayer et al, 1997a,b). We have recently identi®ed an almost intact HERV-K provirus on human chromosome 7 (Mayer et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Germ cell tumors (GCTs) and GCT cell lines express complex splicing patterns of HERV-K (HML-2) transcripts reminiscent of the patterns observed upon infection with exogenous lentiviruses (Lower et al, 1993). GCTs produce large quantities of Gag protein (Sauter et al, 1995) and up to 85% of the patients with GCT produce antibodies directed against the viral Env protein whereas healthy individuals and patients with in¯ammatory diseases or tumors other than GCT very rarely develop such antibodies.…”
Section: Introductionmentioning
confidence: 99%
“…Expression ofpT7-pro0.7 in E. coli BL21DE3 resulted in the autocatalytic cleavage of the pT7-pro0. (Ono et al, 1986;Mueller-Lantzsch et al, 1993;L6wer et al, 1993). All constructs except pT7-pro0.7 and pSPTgag-prot were expressed as TrpE fusion proteins in E. coli.…”
mentioning
confidence: 99%
“…In the present study, we have applied this strategy to the HERV-E family and have identified an active locus that is expressed in normal pancreas and thyroid tissues with enough transcripts for detection by Northern blot hybridization. The expression of HERVs is usually strictly suppressed in normal tissues, and has previ- ously been primarily observed in various tumors and tumor cell lines or predominantly in the placenta among normal tissues (Kato et al 1987;Kjellman et al 1999;Löwer et al 1993Löwer et al , 1996. Therefore, this is, to the best of our knowledge, the first report of predominant expression of HERV in normal tissues other than placenta.…”
Section: Discussionmentioning
confidence: 68%